Legal Certainty of Interfaith Marriage in Indonesia: Harmonizing Religious Law, Constitutional Principles, and Human Rights - Said Lukman Said Lukman; Faisal Sadat S. Harahap; Mospa Darma (International Journal For Advanced Research, 2026)
Interfaith marriage remains one of the most contested issues in the Indonesian legal system due to the interaction between religious law, statutory regulations, constitutional principles, and human rights norms. The absence of explicit legal provisions governing interfaith marriage has created legal uncertainty regarding marriage validity, registration, and the legal protection afforded to interfaith couples. This study aims to analyze the legal certainty of interfaith marriage in Indonesia by examining the harmonization of religious law, constitutional principles, and international human rights. The research employed a normative legal research method using statutory, case, conceptual, comparative, and philosophical approaches. Legal materials were collected through library research from legislation, Constitutional Court decisions, judicial precedents, international legal instruments, and recent scholarly publications and were analyzed qualitatively using doctrinal legal interpretation and prescriptive legal reasoning. The findings indicate that the existing legal framework has not yet provided comprehensive legal certainty due to inconsistent statutory interpretation and administrative implementation. Constitutional Court Decision Number 68/PUU-XII/2014 reaffirmed the constitutional role of religious law in determining the validity of marriage while highlighting the continuing need to balance religious values with constitutional guarantees and human rights. The study concludes that harmonizing marriage law, constitutional jurisprudence, religious legal principles, and international human rights standards is essential to strengthen legal certainty, ensure equal legal protection, and develop a more coherent family law system in Indonesia.